Fate of calcium crystals in alfalfa fed to cattle - L.H. Harbers; G.M. Ward (Kansas Agricultural Experiment Station Research Reports, 1978)
Calcium crystals were located in parallel rows surrounding vascular bundles in alfalfa leaves and under the epidermis of alfalfa stems. The crystals remain intact on vascular bundles in the rumen. Most crystals are dislodged in fecal matter, and free crystals can be recovered. These data support previous work here showing that calcium from alfalfa may be less available to ruminants than previously thought.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Calcium crystals; Alfalfa